Genome wide association study reveals new genes for resistance to striped stem borer in rice (Oryza sativa L.) - Xiang, Xing; Liu, Shuhua; He, Yuewen; Li, Deqiang; Ofori, Andrews Danso; Ghani Kandhro, Abdul; Zheng, Tengda; Yi, Xiaoqun; Li, Ping; Huang, Fu; Zheng, Aiping (Frontiers in Plant Science, 2024)
Rice is one of the most important food crops in the world and is important for global food security. However, damage caused by striped stem borer (SSB) seriously threatens rice production and can cause significant yield losses. The development and use of resistant rice varieties or genes is currently the most effective strategy for controlling SSB. We genotyped 201 rice samples using 2849855 high-confidence single nucleotide polymorphisms (SNPs). We conducted a genome-wide association study (GWAS) based on observed variation data of 201 rice cultivars resistant to SSB. We obtained a quantitative trait locus (QTL)-qRSSB4 that confers resistance to SSB. Through annotation and analysis of genes within the qRSSB4 locus, as well as qRT-PCR detection in resistant rice cultivars, we ultimately selected the candidate gene LOC_Os04g34140 (named OsRSSB4) for further analysis. Next, we overexpressed the candidate gene OsRSSB4 in Nipponbare through transgenic methods, resulting in OsRSSB4 overexpressing lines (OsRSSB4OE). In addition, we evaluated the insect resistance of OsRSSB4OE lines using wild type (Nipponbare) as a control. The bioassay experiment results of live plants showed that after 20 days of inoculation with SSB, the withering heart rate of OsRSSB4OE-34 and OsRSSB4OE-39 lines was only 8.3% and 0%, with resistance levels of 1 and 0, respectively; however, the withering heart rate of the wild-type reached 100%, with a resistance level of 9. The results of the in vitro stem bioassay showed that, compared with the wild-type, the average corrected mortality rate of the SSB fed on the OsRSSB4OE line reached 94.3%, and the resistance reached a high level. In summary, we preliminarily confirmed that OsRSSB4 positively regulates the defense of rice against SSB. This research findings reveal new SSB resistance gene resources, providing an important genetic basis for SSB resistance breeding in rice crops.